Selection of Reference Genes for Quantitative Real-Time PCR in Aquatica leii (Coleoptera: Lampyridae) Under Five Different Experimental Conditions - Yang, Xiao-Jie; Zheng, Hai-Long; Liu, Ying-Yang; Li, Hong-Wei; Jiang, Yu-Hang; Lin, Lian-Bing; Deng, Xian-Yu; Zhang, Qi-Lin (Frontiers in Physiology, 2020)
Aquatic fireflies are important indicators of the quality of freshwater environments and key models for research on insect adaptation to freshwater environments. For these investigations, gene expression analyses using quantitative real-time PCR are heavily dependent on reliable reference genes. In this study, based on a transcriptome assembly and annotation for the aquatic firefly Aquatica leii at the adult and larval stages, 10 candidate reference genes (α-tubulin, β-tubulin, β-actin, EF1A, SDHA, UBQ, GST, GAPDH, RPS31, and RPL13A) were identified for analyses of expression stability. Quantitative real-time PCR analyses for each candidate reference genes in A. leii was conducted for four developmental stages, four adult tissue types, two adult sexes, and two ecological stressors (adults exposed to five temperatures and larvae exposed to four concentrations of benzo(a)pyrene). Results were evaluated by three independent algorithms (geNorm, NormFinder, and BestKeeper) and one comparative algorithm (RefFinder). The expression stability of candidate reference genes in A. leii differed under various conditions. Reference genes with the most stable expressions levels in different tissues, temperatures, sexes, developmental stages, and concentrations of benzo(a)pyrene were α-tubulin, GST, β-actin, β-tubulin, and α-tubulin, respectively. Furthermore, the optimal normalization factors (NFs) for the quantification of the expression levels of target genes by quantitative real-time PCR analyses of A. leii were identified for each experimental group. In particular, NF = 2 for different tissues (α-tubulin + β-tubulin), different sexes (β-actin + EF1A), and larvae exposed to different concentrations of benzo(a)pyrene (α-tubulin + EF1A); NF = 3 for developmental stages (GST + GAPDH + SDHA) and adults exposed to different temperatures (β-tubulin + EFA + GST). In addition, we surveyed the expression profiles of two target genes (CYP3A and CSP8) in larvae exposed to different concentrations of benzo(a)pyrene and in different adult tissues. The results further validated the reliability of the reference genes. The optimal reference genes for various experimental conditions identified in these analyses provide a useful tool for ecological studies of aquatic fireflies.